Work-family conciliation in Perú as a mechanism that promotes the women´s development - Eyzaguirre Rivas, Rocío del Pilar (2020)
Work-family conciliation is a mechanism that has constitutional support in Peru, but it has just been implemented and having importance in the peruvian workplace, during the last years.  Its regulation has been oriented to guarantee equal opportunities between men and women; as well as to achieve an adequate distribution of family and domestic responsibilities.  The incorporation of remote work has put in evidence the difficulty that workers had in conciliate their works with their family life.  In the case of women, the difficulty has been bigger because they have to combine the care of their families with their works and housework too.  So, we must reflect about female identity and female vocation, that must permeate every role that they have to play to achieve their development